Prospects of Hardwood Chip Exports to Japan from the Forests of Godavari Catchment - Seth, V. K. (Indian Forester, 1972)
The pulp and paper industry in Japan has made rapid strides in recent years. It has scored an annual growth rate of 10 per cent and now occupies the world’s third position. Paper and board production is expected 10 rise from 12.2 million tons in 1970 to 35.4 million tons in 1990. The accompanying rise in the requirement of pulpwood would be from 22.7 to 86.7 million cubic metres. Domestic pulpwood production in Japan could not be raised beyond 31.2 million cubic metres. There would be a huge deficit pulpwood in Japan (to the tune of nearly 55 million cubic metres annually). At prresent Japan is importing pulpwood and pulp from several countries. Several new projects are also under way. There is a growing trend for importing pulpwood in the form of chips. Due to tecbnologiical advances and intensive research, the percentage use of hardwood chips is going up rapidly. The paper sets out to describe some of the salient feature of the Japanese pulp and paper industry and some of the recent arrangements made with Australia for the supply of eucalypt chips. India could also play an active role in the matter of supply of hardwood chips to Japan. This trade would be to tbe mutual advantage of both countries. The forests of Godavari catchment are known to contain rich, though undeveloped and uncommitted hardwood resources and it should be possible to export 1 million tons of hardwood chips from these forests to Japan via Vishakhaptatnam, Kakinada and Paradeep Ports. Iron ore is already being exported from these areas, and it is estimated that the value of total exports of iron ore and hardwood chips from tbese areas could be Rs. 930 million annually (Rs. 730 million for iron ore and Rs. 200 million for chips). The investment required for undertaking chip supply to Japan would be around Rs. 40 million. This trade would provide ample employment opportunities in the rural sector and would confer a rich economic value on the hitherto untapped and uncommitted hardwood resources. In addition, this trade would augment the earnings of forest departments and give a much needed boost to the question of intensification of forest management and raising of industrial plantations of fast growing species for the pulp and paper industry The hesitation of the Indian pulp and paper industry for using more and more hardwoods as raw material would be largely removed by the example set by tbe Japanese industry and the way would be paved for the setting up of large new pulping and paper manufacturing units in the hitherto undeveloped forest areas.